Hydrophobic–hydrophilic cross‐linked matrices for controlled release formulation of Highly water‐soluble drug venlafaxine: Synthesis and evaluation studies. Issue 8 (12th June 2018) - Asghar, Saima; Minhas, Muhammad Usman; Ahmad, Mahmood; Khan, Kifayat Ullah; Sohail, Muhammad; Khalid, Ikrima
Abstract: This study was aimed to develop chemically cross‐linked matrix system of polycaprolactone‐co ‐ poly (methacrylic acid) through free radical polymerization method for controlled delivery of highly water‐soluble drug venlafaxine HCl. A hydrophobic polymer, polycaprolactone has been cross‐linked chemically with methacrylic acid by ethylene glycol dimethacrylate (EGDMA) as cross‐linking agent, and benzoyl peroxide was added as reaction initiator. Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy, thermo gravimetric analysis (TGA), differential scanning calorimetry (DSC), and sol‐gel fraction were performed for characterization and structural analysis of polymeric system. Different feed ratios of polycaprolactone, methacrylic acid, and EGDMA were incorporated to investigate the effect of polymer, monomer, and degree of cross‐linking on swelling behavior and release pattern of model drug. pH‐responsive nature of hydrogel was evaluated at low and high pH. FTIR, TGA, and DSC confirmed the formation of new cross‐linked network. pH sensitivity of hydrogel is revealed by increased swelling at pH 7.4. Toxicity study was also performed on rabbits to evaluate cytotoxicity and biocompatibility of developed formulation. Polycaprolactone hydrogels showed low swelling with increased polymer and cross‐linker concentration while swelling increased with high concentration of monomer. Swelling controlled in vitro drug release was found in hydrogels. Gel contents were increased with increase in ratio of polymer, monomer, and cross‐linking agent. Toxicity study endorsed that developed hydrogels were nontoxic and biocompatible.